The effect of obesity on fatty infiltration of the rotator cuff musculature in patients without rotator cuff tears. (May 2019) - Matson, Andrew P.; Kim, Christopher; Bajpai, Swara; Green, Cynthia L.; Hash, Thomas W.; Garrigues, Grant E.
Background: The modified Goutallier classification system describes the fatty infiltration of rotator cuff musculature (RCM) seen on magnetic resonance imaging (MRI) to assist with surgical decision-making for patients with rotator cuff tears (RCT). We describe the relationship between body mass index (BMI) and fatty infiltration in patients without RCT. Methods: Twenty-five patients from each of four different BMI ranges (< 25 kg/m 2 ; 25 kg/m 2 to 30 kg/m 2 ; 30 kg/m 2 to 35 kg/m 2 ; > 35 kg/m 2 ) were randomly selected from 1088 consecutive shoulder MRI scans (T1 parasagittal series). Four physician-readers evaluated MRI scans and assigned modified Goutallier grades (0 to 4) in each of the four rotator cuff muscles, as well as two adjacent muscles. Results: Grade distributions varied significantly based on BMI category for infraspinatus ( p = 0.001), teres minor ( p < 0.001), subscapularis ( p = 0.025), teres major ( p < 0.001) and deltoid ( p < 0.001). Higher grades were evident with a diagnosis of diabetes mellitus in three of six muscles ( p < 0.05), hyperlipidaemia in one muscle ( p = 0.021) and greater patient age in three muscles ( p < 0.05). Conclusions: Obese and severely obese patients without RCT have more fatty infiltration seen on MRI. Patient factors (older age and diagnosis of diabetes mellitus) can be predictive of fatty infiltration in RCM. Fatty infiltration of RCM is not solely attributable to the presence of a RCT.